2022
DOI: 10.1177/08933189211068542
|View full text |Cite
|
Sign up to set email alerts
|

Disciplined Into Hiding: Milk Banking and the “Obscured Organization”

Abstract: Amid recent attention to nonprofit and voluntary organizing, empirical studies have largely focused on social capital functions, decision-making, and volunteer relationships, in contrast to missions or practices that are contested, controversial, or concealed. This study examines how nonprofit milk banks and online milksharing networks experience concealment in unique, unintentional ways. Using ethnographic fieldwork and discursive interviews, we analyze how Discourses of Filth, Suspicion, and (In)adequacy dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Some themes became more salient than others as the authors further examined the data together for emerging themes from patients and their caregivers. Analysis stopped when emergent themes attended to RQ1 and RQ2, provided significant insights into the Digital Coping Model (Rains, 2018), and when new data were not different from what the authors previously identified (Jones & Tracy, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Some themes became more salient than others as the authors further examined the data together for emerging themes from patients and their caregivers. Analysis stopped when emergent themes attended to RQ1 and RQ2, provided significant insights into the Digital Coping Model (Rains, 2018), and when new data were not different from what the authors previously identified (Jones & Tracy, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Human milk is particularly crucial for preterm infants, as it has been shown to reduce the risk of life-threatening complications such as late-onset sepsis (LOS) and necrotizing enterocolitis (NEC) in NICU settings (Mara et al, 2022; Perrin et al, 2022). When breastfeeding is not feasible, wet-nursing and human milk banks (HMBs) serve as important sources of human milk for infants who cannot be breastfed due to reasons related to the mother or the infant (Ergin & Uzun, 2018; Jones & Tracy, 2022).…”
Section: Introductionmentioning
confidence: 99%